The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/01.pra.0000432598.86642.51
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Inpatient Treatment Continuation and Hospital Readmission Rates in Patients with Bipolar Disorder Treated with Aripiprazole or Quetiapine

Abstract: No difference was observed in inpatient antipsychotic treatment continuation and 30-day hospital readmission rates in patients treated with either aripiprazole or quetiapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In the present study, patient race/ethnicity was not found to predict readmission across the time periods examined. This finding is consistent with previous research that found no relationship between race/ethnicity and psychiatric readmission (Appleby et al, 1993;Kreys et al, 2013;Schmutte et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, patient race/ethnicity was not found to predict readmission across the time periods examined. This finding is consistent with previous research that found no relationship between race/ethnicity and psychiatric readmission (Appleby et al, 1993;Kreys et al, 2013;Schmutte et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Among studies that included patients with schizophrenia and/or affective disorders (Appleby et al, 1993; Monnely, 1997; Swett, 1995) as well as studies that only included patients with BD (Kessing et al, 2004; Kreys et al, 2013; Patel et al, 2005), a greater number of prior psychiatric hospitalizations was found to increase the risk of readmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focused on at least one substance use disorder (alcohol dependence, alcohol abuse, alcoholic psychosis, drug dependence, drug abuse, drug psychosis) or inpatients in a substance abuse treatment program with a main alcohol/drug diagnosis or dual diagnosis patients [15, 21–24, 32]. Five studies were restricted to diagnosis of schizophrenia or schizoaffective disorders or psychosis [33–37]; four to diagnosis of affective disorder [19, 26, 38, 39]; two to diagnosis of dementia [18, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…Six papers [17, 28, 35, 39, 48, 66] analysed different aspects of pharmacological treatment (such as dosage or medication prescription), but it resulted significant in only the three of them discussed below and always in bivariate associations. Being on depot injectable antipsychotic medication turned out as a risk factor, while using atypical antipsychotic medication was protective towards readmission [66].…”
Section: Categories Of Pre-discharge Variables Analysedmentioning
confidence: 99%